2019
DOI: 10.32865/fire201951135
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Canada’s Truth and Reconciliation Commission for Indigenous Peoples through Religious Literacy and Spirituality: Unexpected pathways to peace education

Abstract: In 2015, Canada's Truth and Reconciliation Commission (TRC) documented 94 callsto-action in relation to the institutional and debilitating legacy of the Indian Residential School System towards Indigenous culture, language, identity, and knowledge in order to actualize reconciliation between Indigenous peoples and Canada. In it, Justice Murray Sinclair explained that education caused much of the problem but is also part of the solution. Concurrently, the Ontario Human Rights Code (OHRC) updated its policy on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…60-61) (see also Kwok & Selman, 2017). For instance, one pre-post comparison showed that a world religions course reduced inter-group intolerance (discussed in Chan, Akanmori, & Parker, 2019). This is consistent with the theories and findings of large-scale international citizenship education research (Diazgranados-Ferráns & Sandoval-Hernández, 2017;Haste, Bermudez, & Carretaro, 2017;Schulz, Ainley, Fraillon, Kerr, & Losito, 2010).…”
Section: Values Education For What Kind Of Social Cohesion?supporting
confidence: 69%
“…60-61) (see also Kwok & Selman, 2017). For instance, one pre-post comparison showed that a world religions course reduced inter-group intolerance (discussed in Chan, Akanmori, & Parker, 2019). This is consistent with the theories and findings of large-scale international citizenship education research (Diazgranados-Ferráns & Sandoval-Hernández, 2017;Haste, Bermudez, & Carretaro, 2017;Schulz, Ainley, Fraillon, Kerr, & Losito, 2010).…”
Section: Values Education For What Kind Of Social Cohesion?supporting
confidence: 69%
“…The current study examined whether children with autism spectrum disorder (AS) believed in the immutability of species, maintaining that loss was remunerated for by repopulation, with more advanced species coming either from elsewhere or by acts of "special creation". Although these acts could be seen as being in harmony with simultaneous religious beliefs, there was a disinclination to accept that God would allow any of his creations to die out (Chan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%